Impact of a mobile health intervention based on multi-theory model of health behavior change on self-management in patients with differentiated thyroid cancer: protocol for a randomized controlled trial - Jiang, Yang; Sun, Xiangju; Jiang, Maomin; Min, Hewei; Wang, Jing; Fu, Xinghua; Qi, Jiale; Yu, Zhenjie; Zhu, Xiaomei; Wu, Yibo (Frontiers in Public Health, 2024)
Introduction: Theoretical models of health behavior are important guides for disease prevention and detection, treatment and rehabilitation, and promotion and maintenance of physical and mental health, but there are no intervention studies related to differentiated thyroid cancer (DTC) that use theoretical models of health as a guide. In this study, we used a microblogging platform as an intervention vehicle and mobile patient-doctor interactive health education as a means of intervention, with the aim of improving the health behaviors of DTC patients as well as the corresponding clinical outcomes.Methods: This research project is a quantitative methodological study, and the trial will be a single-blind, single-center randomized controlled trial conducted at the